ENHANCING ELEMENTARY SCHOOL STUDENTS’ SPEAKING SKILLS THROUGH CONTEXTUALIZING VOCABULARY IN LUCA CARTOON MOVIES - Abidatul Azizah; Agung Pramujiono; Endah Yulia Rahayu (Widya Mandala Surabaya Catholic University, 2025)
This study examined how well Luca cartoons work to enhance the oral skills of elementary school students, paying special attention to vocabulary and pronunciation. The event took place at a Sidoarjo-based private Islamic elementary school. A mixed method approach including quantitative and qualitative data was used in this investigation. Twenty-five second-graders took part in the study, which used Luca cartoons as a teaching tool for eight treatment sessions. While observations evaluated motivation, engagement, listening comprehension, vocabulary acquisition, emotional reactions, interactions, and follow-up activities, pre-tests and post-tests evaluated vocabulary and pronunciation progress. Both vocabulary (from a mean score of 5.56 before the test to a mean score of 8.26 after the exam) and pronunciation (from a mean score of 5.16 before the test to a mean score of 7.82 after the test) shown notable increases, according to the results. Approximately 91% of the pupils engaged in active participation and shown desire and curiosity. The majority of kids demonstrated strong listening comprehension, picked up new vocabulary, and expressed interest in words they were unfamiliar with. Positive emotional responses made studying English more enjoyable. The students' enthusiastic participation and application of the English expressions they had learnt from the video were demonstrated by the post-film discussion. Although the terminology was not consistently transferred to other settings, the follow-up exercises successfully improved memory and summary abilities. According to the study's findings, adding Luca cartoons to the curriculum can make learning more fun and efficient while also greatly enhancing students' motivation, engagement, and speaking abilities. Thus, it's critical to keep considering individual characteristics when creating new teaching methods to guarantee that every student gains an equal advantage.